Region-specific nitric oxide production in cytosolic and mitochondrial compartments of the rat brain tissues following chronic stress-induced depression-like behavior - Nazaryan, N.S.; Movsesyan, N.H.; Alchujyan, N.Kh.; Movsesyan, H.A.; Guevorkian, A.G.; Hairapetyan, H.L.; Barsegyan, K.A.; Kevorkian, G.A. (Вiopolymers and Cell, 2011)
Aim. To study subcellular nitrergic response in the rat brain regions following chronic stress-induced depression-like behavior. Methods. An animal model of depression induced by chronic circadian stress (CCS) established in our laboratory was used. The L-arginine, L-citrulline and reactive nitrogen species (RNS) levels were
determined spectrophotometrically. Results. Immediately after CCS and four dayslater, а depression-like behavior of rats was observed and accompanied by a substantial persistent elevation of the L-arginine, L-citrulline
and RNS levels with a simultaneous up-regulation of the inducible nitric oxide synthase (iNOS) in both cytosolic
and mitochondrial compartments of the rat prefrontal cortex, striatum, hippocampus, and hypothalamus, and a
down-regulation of their cytosolic constitutive NOS isoforms (cNOS), mitochondrial cNOS was not significantly
changed, with the exception for hypothalamus, in which the latter dropped. Conclusions. Compromised balance
of the L-arginine levels and NO synthesisin both mitochondria and cytosol in the limbic brain appearsto be implicated in the pathogenesis of depression and pathological anxiety.
Keywords: L-arginine, brain, chronic stress, depression-like behavior, mitochondria, nitric oxide synthase. Мета. Вивчення субклітинної нітрергічної відповіді у ділянках
мозку щурів при депресивноподібній поведінці, індукованій хронічним стресом. Методи. Використано розроблену в нашій лабораторії тваринну (щур) модель депресії, індуковану хронічним
циркадіанним стресом (ХЦС). L-аргінін, L-цитрулін і активні
форми азоту (АФА) визначали спектрофотометрично. Результати. Відразу після ХЦС та чотири дні потому спостерігається депресивноподібна поведінка щурів, яка супроводжується значним підвищенням вмісту L-аргініну, L-цитруліну та АФА з одночасним стимулюванням індуцибельної ізоформи NO синтази в мітохондріях та цитозолі префронтального кортексу, стріатуму,
гіпокампа і гіпоталамуса. При цьому відмічено пригнічення загальної активності конститутивних ізоформ NOS (cNOS) у цитозолі
цих відділів мозку, тоді як для мітохондріальної cNOS статистично вірогідних змін не виявлено, за винятком зменшення її активності у гіпоталамусі. Висновки. Порушення вмісту L-аргініну і збалансованого синтезу NO в лімбічному мозку, очевидно, причетні до
патогенезу депресії і тривоги.
Ключові слова: L-аргінін, мозок, хронічний стрес, депресивноподібна поведінка, мітохондрії, синтаза оксиду азоту. Цель. Изучение субклеточного нитрергического ответа в участках мозга крыс при депрессивноподобном поведении, индуцированном хроническим стрессом. Методы. Использовали разработанную в нашей лаборатории животную (крыса) модель депрессии,
индуцированную хроническим циркадианным стрессом (ХЦС).
L-аргинин, L-цитруллин и активные формы азота (АФА) определяли спектрофотометрически. Результаты. Сразу после ХЦС и
четыре дня спустя наблюдается депрессивноподобное поведение
крыс, сопровождающееся значительным повышением содержания L-аргинина, L-цитруллина и АФА, с одновременным стимулированием индуцибельной изоформы NO синтазы в митохондриях
и цитозоле префронтального кортекса, стриатума, гиппокампа
и гипоталамуса. При этом отмечено подавление общей активности конститутивных изоформ NOS (cNOS) в цитозоле этих
отделов мозга, тогда как для митохондриальной cNOS статистически достоверных изменений не выявлено, за исключением
уменьшения ее активности в гипоталамусе. Выводы. Нарушения
в содержании L-аргинина и сбалансированного синтеза NO в лимбическом мозге, повидимому, причастны к патогенезу депрессии
и тревоги.
Ключевые слова: L-аргинин, мозг, хронический стресс, депрессивноподобное поведение, митохондрии, синтаза оксида
азота.